Finite element analysis and improved design of large-scale belt-conveyor drums. Issue 6 (5th December 2016) - Mihailidis, Athanassios; Savaidis, George; Bouras, Emmanouil; Athanasopoulos, Emmanouil; Ganavaras, Nikolaos; Topalidis, Ioannis; Karageorgos, Dimitrios; Rampidis, Ilias
Abstract : Purpose: Large-scale belt-conveyor systems are extensively used in open mines to continuously transport bulk material. Conveyor pulleys are critical components and failures have significant financial consequences due to extended downtime. Aiming at increasing their durability, two critical spots are identified: the drum and the welds between end-plates and drum. Alternative designs have been evaluated. The paper aims to discuss these issues. Design/methodology/approach: Loads on the driving drum are determined from measurements of the bearing force and the motor power. The friction interaction between belt and drum is described by the creep model and its impact is evaluated by comparing the results obtained for low and typical values of friction coefficient. Alternative designs are analysed using finite element method with optimised variable density mesh. The stress field and the deformations are calculated and evaluated. Findings: Friction affects the torque transmission capacity and force distribution, but it is shown that in this case it has almost no impact on the maximum von Mises stress which occurs on the inside surface of the drum; therefore fatigue cracks initiated there, cannot be visually detected. A reinforcing diaphragm is added at the mid-plane to reduce the stress. A new, improved design is proposed to eliminate welds between the end-plates and the drum. Research limitations/implications: The new proposed design has to be tested in the field to ultimately validate its higher durability. Originality/value: The impact of the friction of the belt on the drum is demonstrated. The reinforcement resulting from a mid-plane diaphragm is quantitatively evaluated and assessed. A new improved pulley design is proposed aiming at significantly increased operational life compared to the one of the current design.